Attitudes Toward the Environment and Use of Information and Communication Technologies to Address Environmental Health Risks in Marginalized Communities: Prospective Cohort Study - Jose G Perez-Ramos; Scott McIntosh; Emily S Barrett; Carmen M Velez Vega; Timothy D Dye (JMIR Publications, 2021)
BackgroundInformation and communication technologies, including mobile health (mHealth), can help isolated communities address environmental health challenges. The Puerto Rican island of Culebra has faced multiple sociopolitical and economic factors that have distressed the island's environment and health. Culebrenses are technologically engaged and have demonstrated a use of technology that transcends socioeconomic barriers. As a result, technological interventions could potentially help manage environmental risks on the island. ObjectiveThis study aims to test and evaluate the potential benefits of an mHealth tool, termed ¡mZAP! (Zonas, Acción y Protección), for engaging communities with environmental risks through technology. MethodsParticipants using ¡mZAP! (N=111) were surveyed. Bivariate analyses were used to examine associations of mHealth use with sociodemographics, technology use, an adapted environmental attitudes inventory, and the multidimensional health locus of control. Logistic regression was used to examine associations between attitudes toward environmental health risks and mHealth use. ResultsHigher positive attitudes toward the environment were significantly associated with the use of ¡mZAP! (odds ratio 5.3, 95% CI 1.6-17.0). Environmental attitudes were also associated with the multidimensional health locus of control powerful others subscale (P=.02), indicating that attitudes toward the environment become more negative as feelings controlled by others increase. Participants felt that the authorities would resolve the challenges (63/111, 56.7%). ConclusionsPerceived lack of control could present barriers to collective actions to address salient environmental health challenges in communities. The ongoing dependency on government-based solutions to community problems is worrisome, especially after the hurricane experiences of 2017 (which may potentially continue to be an issue subsequent to the more recent 2020 earthquakes).